'FOR A BROKEN LIMB': FRACTURE TREATMENT IN ANGLO-SAXON ENGLAND. - Russcher, Anne; Bremmer Jr., Rolf H. (Amsterdamer Beiträge zur Älteren Germanistik, 2012)
The treatment of fractures is a relatively simple and logical procedure mastered by many cultures worldwide, so it seems likely prima facie that the Anglo-Saxons would have had some means for treating such injuries as well. To investigate this matter, we shall first describe the modern standards of fracture treatment. Fractures can occur in any type or size of bone, but this paper will focus on long bone fractures, i.e., fractures of the arms and legs, since these were the most likely to be diagnosed correctly by Anglo-Saxon physicians, and hence most likely to received successful treatment. Then, after we describe common methods for treating these injuries in modern medicine, we will next turn to Anglo-Saxon medical literature and its classical sources. Finally, we shall analyse archaeological evidence of fractures in order to gauge the practice of treatment.